Time, flow, and space. (12th December 2019) - Callender, Craig
Abstract: Does a temporal dual process theory explain the illusive flow of time? I point out one shortcoming of such a theory and propose an alternative that does not require either dual cognitive processes or demand such a stark asymmetry between space and time in the brain.